2022
DOI: 10.3390/healthcare10020323
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Jump Tests: A Safe Instrument to Improve the Accuracy of the Functional Capacity Assessment in Robust Older Women

Abstract: Age-related decreases in muscle function lead to disabilities and are associated with negative health outcomes in older people. Although several physical tests can be used to assess physical performance, muscle strength, and power, their interpretation can be hampered by the ceiling effect of some of them. The aim of this study was to assess whether vertical jump tests are safe in terms of physical integrity and whether they are useful in assessing physical performance in forty-one robust older women. The inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
6
14
0
Order By: Relevance
“…Although we did not observe a significant association between circulating creatinine levels and this functional physical test, body weight values were positively correlated with TUGT, demonstrating that heavier volunteers performed worse on the TUGT, both pre- and post-COVID-19-pandemic period. Similar results have been described in the literature [ 11 , 62 ], demonstrating an association between worse strength and balance performance of lower limbs in older adults and increased weight and a higher percentage of body fat. In agreement with the literature, these associations are the result of the negative influence of adipose tissue on the reduction in neuromuscular function in the older adult population [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we did not observe a significant association between circulating creatinine levels and this functional physical test, body weight values were positively correlated with TUGT, demonstrating that heavier volunteers performed worse on the TUGT, both pre- and post-COVID-19-pandemic period. Similar results have been described in the literature [ 11 , 62 ], demonstrating an association between worse strength and balance performance of lower limbs in older adults and increased weight and a higher percentage of body fat. In agreement with the literature, these associations are the result of the negative influence of adipose tissue on the reduction in neuromuscular function in the older adult population [ 63 , 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…Corroborating these data, our group has reported that older women who regularly practiced physical exercises showed improvements in several physical, metabolic, immunological, and redox indices parameters as compared to groups of inactive or sedentary older women [ 8 , 9 , 10 ]. Furthermore, we also demonstrated that the long-standing regular practice of combined-exercise training can maintain functional physical capacity in the older adult population [ 11 ], maintaining their capacity to perform the activities of daily living, which, according to the literature, can improve physical and mental health, socioeconomic independence, and social interactions in this population [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CMJ test ( Bosco et al, 1982 ) was used to assess lower body power. This type of test can be performed safely, without falls or accidents occurring during the test ( Santos et al, 2022 ). The force platform (MuscleLab, Stathelle, Norway) was used to measure take-off height, power, and contact time (CT).…”
Section: Methodsmentioning
confidence: 99%
“…Studies analyzing relationships between physical and functional tests in an elderly population have previously been published ( Singh et al, 2014 ; Orssatto et al, 2020 ; Parsons et al, 2020 ; Staples et al, 2020 ; Santos et al, 2022 ; Abreu et al, 2023 ). However, few studies differentiate between sexes and age ranges ( Buehring et al, 2015 ; Okabe et al, 2021 ; Monjo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cross-sectional studies, Huang et al [10], Nieto-Guisado et al [11], and Souza et al [12] demonstrated the close relationship between physical function, fear/risk of falling, proprioception, and postural control, reinforcing the importance of this type of screen as a means of preventing adverse outcomes associated with falls. Additionally, Santos et al demonstrated the effectiveness of the jump test in assessing muscle strength and power [13], two main factors in developing older adults' physical autonomy. Loss of type II muscle fibers is a primary negative outcome related to health status with aging; thus, the relationship between these losses and the high incidence of falls deserves special mention.…”
mentioning
confidence: 99%